Medicine - Orr, Harry Delphos (My University, 1899)
Introduction: Why did medicine exist? It was born of human sympathy, it sprang from the heart of man and was an evidence of humanity. It survived because its purpose was an end much sought by all. Medicines came in response to the cry of human suffering and took its rise in the practical needs of mankind. Pain was the first lesson in the book of evil which most human beings learned of in the bitterness of sorrow. Greater, by far, than the mystery of life was the mystery of death “In the human ovum which neither chemistry nor the microscope can distinguish from the common mammalian ovum. There dwell a potentialities, species, races, family, and individuality. In that ovum is the assured promise of that goes to make up a perfect organism.
Citation: Orr, Harry Delphos. Medicine. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Preventive Medicine; Sectarianism; Reward; Theses; Manuscripts (documents)